Pulmonary Valve Replacement With Small Intestine Submucosa-Extracellular Matrix in a Porcine Model. (July 2016) - Miller, Jacob R.; Henn, Matthew C.; Lancaster, Timothy S.; Lawrance, Christopher P.; Schuessler, Richard B.; Shepard, Mark; Anderson, Mark; Kovacs, Attila; Matheny, Robert G.; Eghtesady, Pirooz; Damiano, Ralph J.; Boston, Umar S.
Background: Prosthetic materials available for pediatric pulmonary valve replacement (PVR) lack growth potential, inevitably leading to a size mismatch. Small intestine submucosa–derived extracellular matrix (SIS-ECM) has been suggested to possess regenerative properties. We aimed to investigate its function and potential to increase in size as a PVR in a piglet. Methods: An SIS-ECM trileaflet valved conduit was designed. Hanford minipigs, n = 6 (10-34 kg), underwent PVR with an intended survival of six months, with monthly echocardiograms evaluating valve size and function. The conduit was excised for histologic analysis. Results: Of the six, one was sacrificed at three months for midterm analysis, and one at month 3 due to endocarditis. The remaining four constituted the study cohort. The piglet weight increased by 186% (19.56 ± 10.22 kg to 56.00 ± 7.87 kg). Conduit size increased by 30% (1.42 ± 0.14 cm to 1.84 ± 0.14 cm; P < .01). The native right ventricular outflow tract increased by 43% and the native pulmonary artery by 84%, resulting in a peak gradient increase from 10.08 ± 2.47 mm Hg to 36.25 ± 18.80 mm Hg ( P = .03). Additionally, all valves developed at least moderate regurgitation. Conduit histology showed advanced remodeling with myofibroblast infiltration, neovascularization, and endothelialization. The leaflets remodeled beginning at the base with the leaflet edge being less cellular. In addition to the known endocarditis, bacterial colonies were discovered within a leaflet in another. Conclusions: The SIS-ECM valved conduit implanted into a piglet demonstrated cellular infiltration with vascular remodeling and an increase in diameter. Conduit stenosis was a result of slower rates of size increase than native tissue. Suboptimal leaflet performance requires design modifications.